(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Assess the injury status and related characteristics among players at the PVF Football Academy from 2018 to 2020. Research Methods: A descriptive cross-sectional study was conducted involving 230 players enrolled at the PVF Youth Football Training Center from August 2018 to August 2020. Results: The study found that the overall injury incidence rate among male players aged 10 to under 19 was 8,2 injuries per 1,000 hours of training and playing. Notably, the incidence of new injuries during competition was 5,3 times higher than during training sessions. The U18 group had the highest overall injury rate (training injury rate, in-season incidence, number of injuries per player per season, overall injury burden, and injury burden during exercise). The rate of injury during competition peaked in the U14 group and the highest rate of recurrent injury in the U19 group. The burden of competition injuries peaks in the U15 and U14 groups. The rate of contact injuries is highest in the youth age groups U11, U12, U13. Conclusion: Young football players at the PVF Youth Football Training Center are at significant risk of injury, especially during matches. The highest incidence rate of injury during competition is from 13 to under 14 years old, the highest incidence rate of injury during training is from 17 to under 18 years old. Given these findings, it is imperative to implement appropriate prevention and rehabilitation strategies to mitigate injury risks and enhance the overall well-being of players.